KONSEP PENDIDIKAN ANAK DALAM KELUARGA: TELA'AH BUKU BIOGRAFI K.H. IMAM ZARKASYI DARI GONTOR MERINTIS PESANTREN MODERN - Noraina, Noraina; Robi'ah, Robi'ah; Darwis, Muhajir (STAI Darul Qalam Tangerang, 2024)
This research was motivated by the problems of parents with children or families, such as the incidence of teenagers who were addicted to games on mobile phones to undergo outpatient treatment in mental hospitals. The purpose of this study is to determine the concept of child education in the family according to K.H Imam Zarkasyi and its relevance to the education of children in the family today. This type of literature research (Liberary Research) with the study of character thoughts, data collection using documentation techniques obtained from scientific books, journals, and other sources. Then it is analyzed using objective content analysis and hermeneutic methods. The results of this study are (1) the importance of the role of parents in religious education, (2) families must filter the entry of outside negative influences that come through the media, (3) conducive home and space conditions, (4) education using behavioral approach methods (bi al-hikmah wa al-mau'izah al-hasanah), (5)Adhering to the principles of monotheism, morality, and virtuous based on religious morals. The five concepts of child education in the family according to K.H. Imam Zarkasyi are relevant to the education of children in the family today